P-glycoprotein mediated interaction between (R)-[(11)C]verapamil and tariquidar at the human blood-brain barrier studied with positron emission tomography, a comparison with rat data - Bauer, Martin (2011)
Using positron emission tomography (PET) imaging we assessed in vivo the interaction between a microdose of (R)-[(11)C]verapamil, a P-glycoprotein (Pgp) substrate, and escalating doses of the Pgp inhibitor tariquidar (3, 4, 6 and 8 mg/kg) at the blood-brain barrier (BBB) of healthy human subjects. We compared the dose-response relationship of tariquidar in humans with data obtained in rats using similar methodology. Tariquidar was equipotent in humans and rats to increase (R)-[(11)C]verapamil brain uptake, expressed as whole brain volume of distribution (V(T)), with very similar half-maximum effect concentrations. Both in humans and rats, brain V(T)s approached plateau levels at tariquidar plasma concentrations >1,000 ng/mL. However, Pgp inhibition in humans only led to 2.7-fold increase in brain V(T) relative to baseline scans without tariquidar compared to 11.0-fold in rats. The results of this translational study add to the accumulating evidence of marked species-dependent differences in Pgp expression and functionality at the BBB.